Assessment of Changes in Sod Under Intensive Use (Agricultural Engineering, 2017)
The paper presents research results which aimed at evaluation of the change in the sodding degree and selected strength parameters of sod used with varied intensity; additionally sod was modified through administration of biopreparation. Measurements were taken on two types of sod. The first one was formed from perennial rye grass, the second one from orchard grass. It was proved that the use of the investigated facilities resulted in reduction of sodding, which was related to the sod forming species. No impact of biopreparation use on the sodding degree was proved. Intensive use affected the increase of the value of the analysed strength parameters; at low soil moisture (5.0-5.5%) considerable compaction in the surface layer of soil was reported.